2012
DOI: 10.4236/fns.2012.311196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sugar Content in Bottled 100% Fruit Juice versus Extracted Juice of Fresh Fruit

Abstract: This paper presents findings of an experiment for the comparison of sugar concentration in extracted juice of fresh fruit to that of commercially-bottled 100% fruit juice with a "no sugar added" attribute. The goal of the study was to determine if the sugar content of bottled 100% fruit juice with a "no sugar added" label is equivalent to that of extracted juices of fresh fruits. The reported study was performed to address the potential concern that commercially-bottled 100% fruit juices with "no sugar added" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 6 publications
3
25
0
Order By: Relevance
“…The density of rhubarb juice as well as the content of extract were apparently lower as compared to the juices obtained from other fruits. Typical sugar content concentrations in fruits is 7 -26°Brix (Serpen, 2012). Will and Dietrich (2013), using various methods of preliminary treatment prior to pressing, obtained rhubarb juice with extract content of 4-4.8°Brix and density of 1.019-1.022 g/l.…”
Section: Resultsmentioning
confidence: 99%
“…The density of rhubarb juice as well as the content of extract were apparently lower as compared to the juices obtained from other fruits. Typical sugar content concentrations in fruits is 7 -26°Brix (Serpen, 2012). Will and Dietrich (2013), using various methods of preliminary treatment prior to pressing, obtained rhubarb juice with extract content of 4-4.8°Brix and density of 1.019-1.022 g/l.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh unpasteurized juices are aqueous liquids obtained from fruit or vegetable tissue usually extracted manually or mechanically from these raw materials (Nma & Ola, ; Bello, Bello Temitope, Fashola Muibat, & Afolabi, ). Juices in the human diet offer a number of benefits including antioxidants, fiber, phytonutrients, vitamins, and minerals useful in preventing disease (Serpen, ; Tortoe, Johnson, Slaghek, Miedema, & Timmermans, ; Lamport, Saunders, Butler, & Spencer, ). Because of these nutritional benefits, consumers have developed a habit of daily consumption of fresh fruits and vegetables or their juices which have positive impact on health (Bhat & Stamminger, ; Simforian, Nonga, & Ndabikunze, ).…”
Section: Introductionmentioning
confidence: 99%
“…As it was described, LAB are microorganisms with high energy requirements being able to obtain the necessary energy from the fermentation of a wide variety of carbohydrates (Mazzoli et al 2014). Therefore, fruits that contain sugars such as fructose, sucrose, and glucose are favorite sources for LAB development (Serpen 2012). The results also showed that LAB strains belonging to the same species shared a similar carbohydrate fermentation pattern with some differences in the fermentation of galactose, sucrose, and lactose.…”
Section: Discussionmentioning
confidence: 68%